Odpowiedź:
a. 3x + 7 = 2x = 22
5x + 7 =22
5x = 22 - 7
5x = 15
x = 3
b. 8x - 5 - 4r = 15
8x = 15 + 5 + 4r
8x = 20 +4r
x = [tex]\frac{5}{2}+\frac{1}{2}r, reR[/tex]
c. -9 + 7x = 55
7x = 55+9
7x = 64
x = [tex]\frac{64}{7}[/tex] = 9 [tex]\frac{1}{7}[/tex]
d. ?
e. 5,1 + 21 - 9r = 7
26, 1 - 9r = 7
-9r = 7 - 26, 1
-9r = -19,1
r = [tex]\frac{191}{90}[/tex]
1. 6 - 1 - 23 - r = 7
-18 - r = 7
-r = 7 + 18
-r = 25
g. 4,8 - 19 + 2r = 23
-14 , 2 + 2r = 23
2r = 23 + 14,2
2r = 37,2
r = 18,6
b. 7 - 1 + 6 - 5x = 24
12 - 5x = 24
-5x = 24 - 12
-5x = 12
x = - [tex]\frac{12}{5}[/tex]
i. jest okej